KERANG DARAH (Anadara granosa) ABUNDANCE IN COASTAL WATER OF TANJUNG BALAI ASAHAN NORTH SUMATERA - Tanjung, Afrizal; Nurrachmi, Irvina; ', Intan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in December 2012 in Tanjung Balai AsahanCity of North Sumatera Province. This research aim was to know the density of A.granosa. The research used survey method. Collection of A. granosa wasconducted once, that is when ebb period. The sampling was based on the quadrantof 1x1 m² lied on the transect line. Each quadrant was divided into 25 subquadrants with each of 20x20 cm².The results showed that the high abundance was recorded at the middleintertidal zone of station I with the average of 48.3 ind/m². There was nodifference in the cockle density between the upper and middle zones. The t testshowed with the result of 0.603 > 0.05 meaning that there was no diffrencebetween the two zones.Keyword : Anadara granosa, Abudance, Tanjung Balai Asahan, Intertidal